Modulation of the Isoprenoid/Cholesterol Biosynthetic Pathway During Neuronal Differentiation In Vitro. Issue 9 (5th February 2016) - Cartocci, Veronica; Segatto, Marco; Di Tunno, Ilenia; Leone, Stefano; Pfrieger, Frank W.; Pallottini, Valentina
ABSTRACT: During differentiation, neurons acquire their typical shape and functional properties. At present, it is unclear, whether this important developmental step involves metabolic changes. Here, we studied the contribution of the mevalonate (MVA) pathway to neuronal differentiation using the mouse neuroblastoma cell line N1E‐115 as experimental model. Our results show that during differentiation, the activity of 3‐hydroxy 3‐methylglutaryl Coenzyme A reductase (HMGR), a key enzyme of MVA pathway, and the level of Low Density Lipoprotein receptor (LDLr) decrease, whereas the level of LDLr‐related protein‐1 (LRP1) and the dimerization of Scavanger Receptor B1 (SRB‐1) rise. Pharmacologic inhibition of HMGR by simvastatin accelerated neuronal differentiation by modulating geranylated proteins. Collectively, our data suggest that during neuronal differentiation, the activity of the MVA pathway decreases and we postulate that any interference with this process impacts neuronal morphology and function. Therefore, the MVA pathway appears as an attractive pharmacological target to modulate neurological and metabolic symptoms of developmental neuropathologies. J. Cell. Biochem. 117: 2036–2044, 2016. © 2016 Wiley Periodicals, Inc. Abstract : During neuronal differentiation the activity of the MVA pathway decreases.Pharmacologic inhibition of HMGR by simvastatin accelerated neuronal differentiation by modulating geranylated proteins.MVA pathway appears as an attractive pharmacological target to modulate neurological and metabolic symptoms of developmental neuropathologies.